O colapso da função de onda e o confinamento de férmions na inflação taquiônica - Rocha, Julio Cesar Marques da (2022)
In this thesis we approach the spontaneous location collapse model in the tachyonic inflation theory. After a brief immersion in the standard cosmological model, we enter the theory of inflation driven by a tachyonic scalar field, which, while generating the initial expansion, its fluctuations in vacuum are responsible for the emergence of primordial perturbations, necessary for the formation of large-scale structures observed today. In the midst of the transition between the quantum phase and the classical phase, we are faced with the measurement problem, which consists of explaining how the collapse of the wave function occurs in this context. A proposed solution was the theory of collapse by spontaneous location, which proved to be viable and in accordance with current observations. By studying the inflationary regime at low energies, we can analyze the confinement of fermions in tachyonic matter and the correlation between the confinement temperature and the reheat temperature in the inflation-radiation transition.